Design and Fabrication of single band monopole antennafor WLAN applications - Nukhailawi, Yousif Jawad Kadhim; Mohammed ali, Mohammed Abdulmahdi; Salman, FAHAMA Hassoon; Hamzah, Ayad Muslim (International Journal of Psychosocial Rehabilitation, 2020)
This paper introduces a 2.4GHz single-band antenna design. Suggested antenna dimensions are: (13mm x 23mm) for one band. The antenna characteristics, such as gain, long-range radiation patterns and the coupling coefficient, are expressed in the scattering parameter S11. Design and simulation are implemented using FIT-based CST Microwave Studio.